Invasive plants in Minnesota are "joining the locals": A trait‐based analysis. (17th July 2018) - Lodge, Alexandra G.; Whitfeld, Timothy J. S.; Roth, Alexander M.; Reich, Peter B.
Abstract: Questions: Predicting which newly arrived species will establish and become invasive is a problem that has long vexed researchers. In a study of cold temperate oak forest stands, we examined two contrasting hypotheses regarding plant functional traits to explain the success of certain non‐native species. Under the "join the locals" hypothesis, successful invaders are expected to share traits with resident species because they employ successful growth strategies under light‐limited understorey conditions. Instead, under the "try harder" hypothesis, successful invaders are expected to have traits different from native species in order to take advantage of unused niche space. Location: Minnesota, USA. Methods: We examined these two theories using 109 native and 11 non‐native plants in 68 oak forest stands. We focused on traits related to plant establishment and growth, including specific leaf area (SLA), leaf carbon‐to‐nitrogen ratio (C:N), wood density, plant maximum height, mycorrhizal type, seed mass and growth form. We compared traits of native and non‐native species using ordinations in multidimensional trait space and compared community‐weighted mean (CWM) trait values across sites. Results: We found few differences between trait spaces occupied by native and non‐native species. Non‐native species occupied smaller areas of trait space than natives, yet were within that of the native species, indicating similar growth strategies. We observed a higher proportion of non‐native species in sites with higher native woody species CWM SLA and lower CWM C:N. Higher woody CWM SLA was observed in sites with higher soil pH, while lower CWM C:N was found in sites with higher light levels. Conclusions: Non‐native plants in this system have functional traits similar to natives and are therefore "joining the locals." However, non‐native plants may possess traits toward the acquisitive end of the native plant trait range, as evidenced by higher non‐native plant abundance in high‐resource environments. Abstract : Non‐native plants in Minnesota's oak forests are "joining the locals" by applying similar growth strategies. However, non‐native plants may possess traits toward the acquisitive end of the native plant trait range, as evidenced by higher non‐native plant abundance in high‐resource environments.